THE INTEGRATION OF TELEROBOTIC SYSTEM WITH VIRTUAL REALITY SIMULATION AND GESTURE TRACKING SENSOR - VICTOR SINAGA (NIM : 13313043) - NADYA FEBIANI (NIM : 13313069),
Telerobotic system development increased significantly for functions and purposes, supported by development of the technology platform and open resources . Current technology which has these two important points, one of it is mobile Virtual Reality through the implementation in the smartphone. With Virtual Reality technology, intuitively controlling robot system using the immersion of the user with the Virtual Reality itself could be created . This study aims to design the conceptualization of intuitive and immersive telerobotic system so as if the user can control the telerobotic system directly through the cyber space created by the virtual reality simulation . The telerobotic system consist of two main parts, those are arm-type robot with 3 degree of freedom (3DOF) using MeArm robot prototype design powered by servo motor analog-feedback which similtaneously functioning as actuator and sensor because of the internal potentiometer it has also having a clamp as itÃ‚Â’s end effector. The second part is mobile robot consist of the acrillic chassis and DC motor representing dynamic movement of the robot. This robot can be controlled remotely and wirelessly using WiFi and internet connection by user through Virtual Reality application. The designed telerobotic system of the arm-type robot has the accuracy of motor servo 1 (γ) = 80,45%, %, motor servo 2 (α) = 99,29%, motor servo 3 (β) = 89,05%, and the mobile-type robot has the accuracy of motor DC 1 = 78,37%, and motor DC 2 = 81,67%.